2017
DOI: 10.4049/jimmunol.1700410
|View full text |Cite
|
Sign up to set email alerts
|

On the Role IL-4/IL-13 Heteroreceptor Plays in Regulation of Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) manifests when the insulin-producing pancreatic beta-cells are destroyed as a consequence of an inflammatory process initiated by lymphocytes of the immune system. The non-obese diabetic (NOD) mouse develops T1D spontaneously and serves as an animal model for human T1D. The heteroreceptor (HR), comprising IL-4Rα and IL-13Rα1, serves both IL-4 and IL-13 cytokines which are believed to function as anti-inflammatory cytokines in T1D. However, whether the HR provides a responsive element to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…31,32 Conversely, inhibiting the IL-4/IL-13 pathway via genetic deficiency of IL-4Ra or the IL-4Ra/IL-13Ra1 heteroreceptor is effective in controlling the blood glucose levels and islet inflammation. 33,34 The proposed mechanism suggests that IL-4Ra/IL-13Ra1 receptor deficiency increases the frequency of mTGFb + Foxp3 int Tregs and the persistence of CD206 + macrophages in the pancreas. 33 These results seem to fuel a debate about the controversial functions of these cytokines in the control of diabetogenic responses.…”
Section: Type-2 Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Conversely, inhibiting the IL-4/IL-13 pathway via genetic deficiency of IL-4Ra or the IL-4Ra/IL-13Ra1 heteroreceptor is effective in controlling the blood glucose levels and islet inflammation. 33,34 The proposed mechanism suggests that IL-4Ra/IL-13Ra1 receptor deficiency increases the frequency of mTGFb + Foxp3 int Tregs and the persistence of CD206 + macrophages in the pancreas. 33 These results seem to fuel a debate about the controversial functions of these cytokines in the control of diabetogenic responses.…”
Section: Type-2 Cytokinesmentioning
confidence: 99%
“…33,34 The proposed mechanism suggests that IL-4Ra/IL-13Ra1 receptor deficiency increases the frequency of mTGFb + Foxp3 int Tregs and the persistence of CD206 + macrophages in the pancreas. 33 These results seem to fuel a debate about the controversial functions of these cytokines in the control of diabetogenic responses. IL-4 and IL-13 are examples of cytokines that can target the same part of a receptor and perform overlapping functions; thus, blocking the affected receptors may produce multiple effects on the inflammatory process, which are not completely clarified.…”
Section: Type-2 Cytokinesmentioning
confidence: 99%
“…IL-4 and IL-13 function to modulate autoimmunity. Furthermore, the IL-4/IL-13 pathway contributes to maintenance of peripheral tolerance and restrains development of T1DM [46]. PTPN2 is highly expressed in immune-related cells and its expression is modified in CD4+ T cells and more than 10 genetic regions in PTPN2 that demonstrate susceptibility to T1DM have been identified [47].…”
Section: Non-hla Genes Associated With T1dmmentioning
confidence: 99%
“…We have previously demonstrated that the IL-4Rα/IL-13Rα1 heteroreceptor (HR) contributes to the development and function of APCs including macrophages [4, 12] and neonatal DCs as well as basophils[13]. Herein, comparative analysis was performed in HR +/+ and HR −/− mice to determine whether the HR plays a role in populating the thymus with functional APCs.…”
Section: Resultsmentioning
confidence: 99%